1998
DOI: 10.1074/jbc.273.52.34730
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Anticoagulant Mechanisms of a Covalent Antithrombin-Heparin Complex

Abstract: Recently, we developed a covalent antithrombin-heparin complex (ATH) as a possible treatment for respiratory distress syndrome. ATH reacted rapidly with thrombin and efficiently catalyzed the inhibition of either thrombin or factor Xa by exogenous antithrombin. In order to investigate mechanisms for the conjugate's unusual anticoagulant properties, changes in fluorescence due to covalent linkage or addition of exogenous antithrombin were studied in relation to reaction with thrombin derivatives or factor Xa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…There is strong evidence from a number of experiments that ATH preparations contain multipentasaccharide GAGs. First, titration of ATH by AT resulted in a 30 -40% increase in intrinsic fluorescence, which is characteristic of AT activation by pentasaccharide binding (11,14). Second, gel filtration of the non-covalent complexes formed between the heparin released from ATH by protease treatment and excess free AT showed that ϳ30% of the heparin molecules were capable of binding Ն2 AT molecules (14).…”
Section: Unfractionated Standard Heparin (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence from a number of experiments that ATH preparations contain multipentasaccharide GAGs. First, titration of ATH by AT resulted in a 30 -40% increase in intrinsic fluorescence, which is characteristic of AT activation by pentasaccharide binding (11,14). Second, gel filtration of the non-covalent complexes formed between the heparin released from ATH by protease treatment and excess free AT showed that ϳ30% of the heparin molecules were capable of binding Ն2 AT molecules (14).…”
Section: Unfractionated Standard Heparin (H)mentioning
confidence: 99%
“…Thus, one possible mode for ATH catalysis of factor Xa/thrombin inhibition would be via the activation of added AT molecules by the pentasaccharide site proximal to the AT component of ATH. However, because of the rapid velocity of the direct thrombin (factor Xa) ϩ ATH reaction (second order rate constants for thrombin ϩ ATH and factor Xa ϩ ATH are 3.0 ϫ 10 9 and 2.4 ϫ 10 8 M Ϫ1 min Ϫ1 , respectively (14)), thrombin-ATH (or factor Xa-ATH), inhibitor complexes might be generated before several cycles of the catalytic reaction could take place. Once factor Xa or thrombin had formed a covalent bond with the AT portion of ATH, approach by free serpin and enzyme to the inhibited ATH may be restricted due to steric reasons.…”
Section: Unfractionated Standard Heparin (H)mentioning
confidence: 99%
“…Human plasma AT (Affinity Biologicals, 5.1 mg/ml) and ATH (9.0 mg/ml) were used for the preparation of L-AT and L-ATH, respectively, by a modification of the method described previously (11,21). Briefly, both AT and ATH were dialyzed against 0.25 M sodium citrate, 10 mM Tris ⅐ HCl, pH 7.4, for at least 24 h at 23°C.…”
Section: Methodsmentioning
confidence: 99%
“…ATH was prepared as described previously (11,21). Briefly, 1 mg/ml of human AT (Affinity Biologicals, Ancaster, ON, Canada) and 56 mg/ml of aldose-containing unfractionated heparin (UFH; Sigma, Mississauga, ON, Canada) were heated in PBS at 37°C for 14 days, followed by purification involving hydrophobic chromatography on butyl-sepharose (Amersham Biosciences, Uppsala, Sweden) before anion exchange on DEAE-sepharose (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation